(untitled) (KIUT Publication, 2025)
The article analyzes the practical effectiveness of financial incentives in the process of implementing green technologies by small business entities. During the analysis, various forms of subsidies, tax incentives, grants, loans, and government guarantees are examined, and their impact on small business development is evaluated based on empirical data. In addition, the strengths and weaknesses of the existing financial incentive system in Uzbekistan are identified, and improvement directions are proposed based on advanced international experience. The main outcome of the article is the identification of opportunities to develop an effective model of financial support mechanisms for small businesses in the transition to a green economy.